Pelatihan Manajemen Sumber Daya Manusia Kelompok Sadar Wisata (Pokdarwis) Di Desa Wisata Suntenjaya Kecamatan Lembang Kabupaten Bandung Barat (Jurnal Sosial & Abdimas, 2022)
The tourism potential in Suntenjaya Tourism Village, Lembang District, West Bandung Regency is very large, but it has not been fully managed professionally, so it has not been able to support regional acceptance in Sunten Jaya Tourism Village, Lembang District, West Bandung Regency, especially in improving the standard of living of the local community. Sunten Jaya Tourism Village, Lembang District, West Bandung Regency, especially POKDARWIS Eka Harapan, Sunten Jaya Village, Lembang District, West Bandung Regency, is very interested in efforts to develop regional tourism so that it indirectly has a very strategic role in realizing efforts towards its development. The existence of the Human Resource Management Training Program in the Pokdarwis Mentoring Program in Sunten Jaya Tourism Village, Lembang District, West Bandung Regency is one of the Community Service (PkM) Stiepar Yapari in order to improve the Resource Management used in POKDARWIS Eka Harapan Village Sunten Jaya District Lembang Regency West Bandung is more comprehensive in the sense that it focuses more on improving existing Resource Management.